Задача про математичний сейф та її розв'язання (частина 1) - Кривий, С.Л.; Гогерчак, Г.І. (Кібернетика та комп’ютерні технології, 2020)
Робота присвячена розв’язанню задачі про математичний сейф. Розглядається математична постановка задачі про математичний сейф, де показано що її розв’язання зводиться до розв’язання систем лінійних рівнянь у скінченних кільцях та полях. Також розглядаються методи та алгоритми розв’язання такого типу систем, де наводяться методи та алгоритми побудови базису множини розв'язків систем лінійних рівнянь для цих областей та приклади для ілюстрації їх роботи. The purpose of the article is to formulate a mathematical model of the mathematical safe problem and its reduction to systems of linear equations in different domains; to consider solving the corresponding systems in finite rings and fields; to consider the principles of constructing extensions of residue fields and solving sys-tems in the relevant areas. Results. The formulation of the mathematical safe problem is given and the way of its reduction to sys-tems of linear equations is considered. Methods and algorithms for solving this type of systems are considered, where exist methods and algorithms for constructing the basis of a set of solutions of linear equations and de-rivative methods and algorithms for constructing the basis of a set of solutions of systems of linear equations for residue fields, ghost rings, finite rings and finite fields. Examples are given to illustrate their work. The principles of construction of extensions of residue fields by the module of an irreducible polynomial, and ex-amples of operations tables for them are considered. The peculiarities of solving systems of linear equations in such fields are considered separately. All the above algorithms are accompanied by proofs and estimates of their time complexity.